Verworfene Frauenzimmer-- Geschlecht als Kategorie des Wissens vor dem Strafgericht - Grütter, Melanie (Gender Studies, 2017)
How the construction of female sexuality in connection with criminal acts still (re)produces gender stereotypes in law and the judicial system even today.